At dawn we slept : - Prange, Gordon William (Penguin Books, 1982)
At 7:53 a.m., December 7, 1941, America's national consciousness and confidence were rocked as the first wave of Japanese warplanes took aim at the U.S. Naval fleet stationed at Pearl Harbor. As intense and absorbing as a suspense novel, At Dawn We Slept is the unparalleled and exhaustive account of the Japanese bombing of Pearl Harbor. It is widely regarded as the definitive assessment of the events surrounding one of the most daring and brilliant naval operations of all time. Through extensive research and interviews with American and Japanese leaders, Gordon W. Prange has written a remarkable historical account of the assault that-sixty years later-America cannot forget.